Recommendations for traveling to altitude with neurological disorders. (19th November 2021) - Falla, Marika; Giardini, Guido; Angelini, Corrado
Background: Several neurological conditions might worsen with the exposure to high altitude (HA). The aim of this review was to summarize the available knowledge on the neurological HA illnesses and the risk for people with neurological disorders to attend HA locations. Methods: A search of literature was conducted for several neurological disorders in PubMed and other databases since 1970. The neurological conditions searched were migraine, different cerebrovascular disease, intracranial space occupying mass, multiple sclerosis, peripheral neuropathies, neuromuscular disorders, epileptic seizures, delirium, dementia, and Parkinson's disease (PD). Results: Attempts were made to classify the risk posed by each condition and to provide recommendations regarding medical evaluation and advice for or against traveling to altitude. Individual cases should be advised after careful examination and risk evaluation performed either in an outpatient mountain medicine service or by a physician with knowledge of HA risks. Preliminary diagnostic methods and anticipation of neurological complications are needed. Conclusions: Our recommendations suggest absolute contraindications to HA exposure for the following neurological conditions: (1) Unstable conditions–such as recent strokes, (2) Diabetic neuropathy, (3) Transient ischemic attack in the last month, (4) Brain tumors, and 5. Neuromuscular disorders with a decrease of forced vital capacity >60%. We consider the following relative contraindications where decision has to be made case by case: (1) Epilepsy based on recurrence of seizure and stabilization with the therapy, (2) PD (± obstructive sleep apnea syndrome-OSAS), (3) Mild Cognitive Impairment (± OSAS), and (4) Patent foramen ovale and migraine have to be considered risk factors for acute mountain sickness.